Efficiency of Advanced Membrane Wastewater Treatment Plant towards Removal of Aspirin, Salicylic Acid, Paracetamol and p-Aminophenol - Khamis, Mustafa (2011)
The efficiency of membrane separation technology for wastewater treatment was employed to check its efficiency in removing pharmaceuticals, their degradation products and their metabolites from wastewater. Aspirin and paracetamol were found to degrade in wastewater furnishing salicylic acid and p-aminophenol, respectively. The kinetics for the degradation reactions of both drugs were investigated in wastewater environment and both have shown first order kinetics with rate constants 0.845 × 10-8 Ms-1 and 1.0 × 10-8 Ms-1 at room temperature, respectively. These values are an order of magnitude larger than those obtained in pure water under the same conditions. The over all performance of the plant has shown complete removal of these compounds from spiked wastewater within the detection limit of the analytical method. The most effective components for removing those drugs within the plant were activated carbon and clay micelle filters. The adsorption isotherms for these compounds have been studied using both activated carbon and newly developed adsober named clay-micelle complex. All studied isotherms were found to fit Langmuir isotherm. The Langmuir constant and the adsorption capacity were evaluated and discussed.